The Relevance of Paul's Preaching Activities in Athens to the Preaching of the Church Based on Acts 17:16-34 - Bonaventura Priyo Sutejo; R.F. Bhanu Viktorahadi Pr. (Khazanah Sosial, 2022)
One of the reporting strategies is dialogue. Acts 17:16-34 describes Paul's dialogical way of proclaiming the Gospel to the Athenians. First, he used public spaces to meet, communicate, and interact with Athenians. Second, he regarded the Athenians as partners in discussion. Third, he used the richness of local Athenian culture as an entry point for his sermons and corrected them. In this way, Paul knew and understood their mindset and lifestyle. Although it has not succeeded in converting the Athenians, it offers an alternative preaching strategy. The next question is how this strategy can be applied today. This paper uses the text analysis method to find the stages of the procedure used in current reporting. Thus, the proclamation of the Church not only elevates the context of society but also makes a positive contribution to them. Therefore, Paul's narrative in Acts 17:16-34 can be a model approach for the Church to realize a dialogical proclamation.